Experiences of mothering from prison; a qualitative evidence synthesis - Walsh, Amy (The journal of forensic psychiatry & psychology, 2023)
Maternal incarceration can be a disruptive process for the entire family. Incarcerated mothers experience stigma and are often regarded both as criminals and mothers who willingly abandoned their children. There have been several studies examining the impact on the children of incarcerated parents. However, a synthesis of qualitative studies exploring the lived experience of these women is lacking. This systematic review seeks to provide a qualitative evidence synthesis of the literature. The following research question guided the review; what are the experiences and perceptions of being a mother in prison while separated from your children. Using the thematic synthesis method, data from 15 studies were analysed. Four analytical themes were found: ‘Barriers to Motherhood’, ‘Burden of Perceived Maternal Failure’, ‘Salvation through Motherhood’ and ‘A Better Future’. Motherhood was both the source of a perceived failing and offered redemption for the incarcerated women. As such, this review supports evidence that the mothering role should be encouraged and facilitated while these women are in prison.